MODIFICATION OF TYRE MACHINE SYSTEM WITH MITSUBISHI PLC AUTOMATIC FOOT LENGTH GAUGE - Hayadi Hamuda; Taufik Iqbal Miftaks; Lailatun Adzimah; Encik Yoega Renaldi; Muhammad Riza Syahputra; Novia Permata Atmadja (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
One of the steps in the tyre manufacturing process is the Tyre Building Machine. The tread is the last component to be fitted to the tyre carcass after all other components have been installed. When measuring the length of the pre-adjusted tread, errors or variations often occur in the measurements taken by the measuring device due to its lack of accuracy. This prevents operators from using the tyre tread and can result in a large amount of scrap and wasted time during the tyre manufacturing process. To overcome this problem, a redesigned tread length measurement system with a higher level of accuracy was created to minimise tread length fluctuations during tyre manufacturing. The results of the tread length measurement procedure using the ENC-1-1-24-N type rotary encoder can function according to the program created. This is validated by the tread length measurement data. The results of the HMI display design and the software created can operate according to the desired instructions. To change the tread length, the operator only needs to enter the number on the HMI panel.